Muerte en el parque : cementerios de Buenos Aires (1935-1965) - Dal Castello, David (2022)
In order to transform Chacarita, Recoleta and Flores cemeteries, the Municipality of the City of Buenos Aires commissioned new projects to its technical offices in 1935. Between 1935 and 1965, several projects were presented and, despite their differences, they all shared the same common aspiration to form ?park cemeteries?. The object of study of this thesis are the Public Park Cemetery projects. We believe that this study will contribute to the knowledge of the official death and urban cemeteries representations, made by municipal professionals and technicians. This tesis will also contribute to the expansion of the historical record of urban modernization processes, since those projects have acquired little relevance and visibility in disciplinary historiography.\nBased on these observations, we hypothesize that the Public Park Cemetery was a significant piece of the Buenos Aires modernizing project: through the figure of the park it was sought to transform and reconcile the cemeteries with the City, to supply the greater demand for graves, to purify and attenuate the instituted aesthetics of death, and broadening the field of action of modern architectures on funeral programs. This was an important challenge given that the dominant imaginary of eternity and stability in those pre-existing cemeteries, and in Buenos Aires society in general, opposed and disbelieved the aesthetic capacities, scientist-based methods and techniques promoted by public management and architectural modernity to represent death.\nThat is why we propose to discuss the Public Park Cemetery project as a representative program of the modern city in Buenos Aires, the incorporation and ways of linking new actors and knowledge to state bureaucracies and the historical processes of collective production of the city and architecture. Starting from its critical treatment, we will seek to formulate an idea of "funerary space" as a theoretical-methodological category that would allow to stablish a dialogue between the projectual and funerary fields.\nAs public works and goods, the Public Park Cemeteries differed in many respects from the private park cemeteries created since the 1980s in the outskirts of Buenos Aires. The Public Park Cemeteries emerged decades before, as a practical solution to the lack of physical space in cemeteries and to a certain moral and aesthetic need to transform the urban image of death. These processes occurred in the interaction and exchange between multiple actors, that is to say, it was a collective work of a specific political and technical culture. So, why transforming existing cemeteries? How? And what ideas of death, city and architecture did these transformations imply? will be the central questions that organize the narrative of this thesis.